Developing a conceptual framework of building maintenance driving factors for effective heritage building maintenance programme in Malaysia - Syed Mohamad, S B H; Rahman, M A A; Suratkon, A; Deraman, R; Zakaria, M N (2023)
The purpose of this research concept paper is to explain the initial development process of a proposed conceptual framework of building maintenance driving factors for an effective heritage building maintenance programme. The maintenance programme is the most important phase in arranging the building maintenance management process. The heritage building value always will decrease within a period of time. If the relevant maintenance procedure fails to detect the root causes of building deterioration, it will have a significant impact on the durability and strength of heritage buildings. This research is initiated in order to search further on the significant effective maintenance driving factors. The maintenance driving factors will be the indicators in filling the gap for improving the heritage building maintenance programme and comprehensive heritage maintenance framework. The aim of this research is to develop a comprehensive framework that depict the significant driving factors of the effective building maintenance programme for a heritage building in Malaysia. The research objectives are to investigate the significant driving factors which are involved in the maintenance programme and to examine the significant connection between the driving factors in developing an effective maintenance programme for heritage buildings in Malaysia. The relevant research data collection has been obtained by conducting expert opinion interviews and findings from literature reviews. Several factors have been identified as the enablers of the effective heritage building maintenance programme, and clustered into 4 main factors (Human Factor; Management Factor; Organisational Factor, and Technology Factor). In conclusion, the research will be able to give significant findings regarding the driving factors involved in the development of a conceptual framework for an effective heritage building maintenance programme